Mathematical analysis of leakage current level in correlation with environmental stresses for solid insulating material under tracking test - M. Piah, M. A.; Darus, Ahmad (2004)
Environmental pollution can cause the insulator material to become progressively coated with dirt and chemicals in the long run. In the presence of wet atmospheric conditions, the leakage current flows due to the development of conducting path across the insulator surface. The level of leakage current depends on the surface wetting and the degree of electrolyte contamination as well as the environmental factors. An analytical approach based on dimensional analysis technique is applied to develop a mathematical model of leakage current in correlation with the environmental stresses. In order to verify the developed model, an inclined-plane tracking test is conducted on the polymeric insulating materials. The experimental work is carried out by measuring the magnitude of surface leakage current at different levels of contamination. Simulation results of the model have shown good agreement to the experimental results and provide useful information on describing the test condition of the tracking test procedures.